Paradigma dan Konsep Integrasi Ilmu - Qorina, Ulfa; M, Marilang; Nonci, M Hajir (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The paradigm and concept of knowledge integration are linked to high specialization in various disciplines, causing fragmentation of knowledge. This creates challenges in dealing with the complexity of global problems that cannot be solved with a single discipline approach. A new paradigm is needed that encourages the integration of knowledge to address complex problems in a holistic and coordinated way. The integration of knowledge is crucial in facing the dynamics of the times that demand comprehensive and collaborative solutions.